2009
DOI: 10.1007/s00449-009-0373-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological synthesis of platinum nanoparticles using Diopyros kaki leaf extract

Abstract: The leaf extract of Diopyros kaki was used as a reducing agent in the ecofriendly extracellular synthesis of platinum nanoparticles from an aqueous H(2)PtCl(6).6H(2)O solution. A greater than 90% conversion of platinum ions to nanoparticles was achieved with a reaction temperature of 95 degrees C and a leaf broth concentration of >10%. A variety of methods was used to characterize the platinum nanoparticles synthesized: inductively coupled plasma spectrometry, transmission electron microscopy, energy-dispersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
147
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(154 citation statements)
references
References 22 publications
5
147
0
2
Order By: Relevance
“…Song et al attempted to create PtNPs using the leaf extract of Diopyros kaki. A greater than 90% reduction of Pt ions into nanoparticles was illustrated in approximately 2.5 hours [73]. Song and group suggested that the reduction of the Pt ions was due to the presence of functional groups within the leaf extract such as amines, alcohols, ketones and carboxylic acids; as opposed to an enzyme mediated process.…”
Section: Nanoparticle Synthesis By Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al attempted to create PtNPs using the leaf extract of Diopyros kaki. A greater than 90% reduction of Pt ions into nanoparticles was illustrated in approximately 2.5 hours [73]. Song and group suggested that the reduction of the Pt ions was due to the presence of functional groups within the leaf extract such as amines, alcohols, ketones and carboxylic acids; as opposed to an enzyme mediated process.…”
Section: Nanoparticle Synthesis By Plantsmentioning
confidence: 99%
“…Song and group suggested that the reduction of the Pt ions was due to the presence of functional groups within the leaf extract such as amines, alcohols, ketones and carboxylic acids; as opposed to an enzyme mediated process. This was based on the fact that the reaction temperature was 95°C and no protein peaks were found in their FTIR analysis [73].…”
Section: Nanoparticle Synthesis By Plantsmentioning
confidence: 99%
“…The peaks at 1000-1200 cm À1 correspond to C-O/C-OH single bonds of alcohols [39,40] and phenols [41]. The absorbance peak at 1055-1066 cm À1 corresponds to C-N stretching vibration of aliphatic amines or to alcohols/phenols [22].…”
Section: Ftir Analysis Identified Gnp-associated Moleculesmentioning
confidence: 99%
“…The bands in 1315-1380 cm À1 range indicate the OH deformation vibrations in the aromatic ring/phenol [42,43]. The peak at 1619-1638 cm À1 corresponds to C¼C groups or aromatic rings of polyphenols [41,44] or carbonyl groups [44]. The peak at 3407-3433 cm À1 corresponds to OH group of polyphenols [39].…”
Section: Ftir Analysis Identified Gnp-associated Moleculesmentioning
confidence: 99%
“…Nanochemistry mainly focuses on the synthesis of various metal nanoparticles like gold, silver, zinc, platinum [2][3][4][5], etc., due to its unique properties, which opens a new venue for the production of nanodevices, therapeutics, drugs, etc., in the field of nanomedicine and nanobiotechnology [6][7][8][9][10][11][12]. Gold nanoparticles have diverse applications in cancer treatment, electrochemical sensors, biosensors, gene and drug delivery, catalysis, etc., [13,14].…”
Section: Introductionmentioning
confidence: 99%